Social desire and physical and psychological manifestations and their relationship to the performance of artistic gymnastics skills for the female students in the faculty of physical education (Journal of Physical Education (Maringá), 2019)
knowing the desire of  female students to belong to the community through the social desirability, and to identify the physical psychological manifestations and this is reflected in the level of performance of artistic gymnastics skills on the four devices, the relationship between the social desire and the physical psychological manifestations and  performance of the artistic gymnastics skills, sample of the research female students of the second stage in the faculty of physical education and sports sciences at the University of Babylon with number (30), the results showed that the social desire and the performance of artistic  gymnastics skills in the moderate level, physical psychological manifestations in the higher level, and a direct  relationship between social desirability and performance of artistic gymnastics skills, and inverse relationship between the physical psychological manifestations with the skills of ground movements and  direct with  skills of the other devices.